DEVELOPMENT OF ASSESSMENT CRITERIA FOR STUDENTS STRATEGIC COMPETENCE IN SPEAKING ENGLISH LANGUAGE - Kaharova Shahlo Shaydilloevna (Galaxy International Interdisciplinary Research Journal, 2022)
The problem of assessing the strategic competence of students in the English language speaking. The components of the strategic competence of students, a number of factors, which influences the speaker’s strategic behavior. The scales that are widely are used to assess speech competence in speaking in accordance with its strategic aspect. The key features of the assessment of strategic speaking are indicated, suggested cognitive, communicative, expedient and educational-compensatory assessment, criteria, strategic competence with their corresponding indicators.